PEMEROLEHAN BAHASA PADA ANAK USIA 10-12 TAHUN DI SDN 047 BALONGGEDE KOTA BANDUNG (KAJIAN PSIKOLINGUISTIK) - Fahman Nur Faizi; Kharisma Bintang Destriadi; Yoga Prima Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study investigates the language acquisition of children aged 10-12, focusing on their linguistic development in morphology, syntax, semantics, and pragmatics. Conducted at SDN 047 Balonggede, Bandung, the research employs a qualitative descriptive method. Data was collected through observation of four students during classroom activities. The findings reveal that children at this age demonstrate significant advancements in language acquisition. Their ability to form complex sentences, use appropriate morphological structures, and comprehend both literal and contextual meanings highlights their developing linguistic competence. However, challenges such as discrepancies between academic language and daily communication, as well as the influence of technology on language development, were also identified. These findings underline the importance of tailored teaching materials that reflect children's existing linguistic abilities. The study concludes that an immersive language environment and active interaction are crucial for facilitating effective language acquisition in children aged 10-12.